Energy production using solar-powered electrolyzer and hydrogen fuel cell / Teoh Wei Hern... [et al.] - Teoh, Wei Hern; Abdullah, Samihah; Abdul Hamid, Shabinar; Fadhlullah, Salahuddin Yusuf (Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
This study presented the implementation of a small-scale (50 W) solar energy harvesting system coupled with an electrolyzer and proton exchange membrane (PEM) fuel cell. The energy from the solar panel would be utilized by the electrolyzer to produce hydrogen gas. The hydrogen gas would be used, in turn, by the PEM fuel cell to generate electricity which supports both DC and AC load. Excess energy from the solar panel is also used to charge the lead-acid backup battery. Analysis of the system showed that 400 mL of hydrogen gas could be produced within every 17 minutes in optimal conditions; between 11 am until 4 pm with bright sunlight. For every 400 mL of hydrogen gas, the PEM fuel cell could sustain continuous operation of a 5V 500 mA DC load for 95 seconds. Theoretically, more than 7000 mL of hydrogen gas could be produced within 5 hours in strong sunlight, which could power up a 50 mA and 500 mA load for 4.7 hours and 28 minutes respectively, during evening or night operations. The proposed system could complement the traditional battery-based storage system while remaining as a clean source of energy production.